The Protection of Human Rights in the Council of Europe – The European Convention on Human Rights in General Terms - Karakamisheva-Jovanovska, Tanja (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
Тhe Council of Europe (CoE) mission is to keep the peace in Europe and protect human rights and freedoms. It tackles, systematically, the root causes of tensions and disputes before they erupt into conflicts. The consequences of the Second World War (WWII) on the European continent were one of the main reasons for establishing the CoE, as human rights were under serious threat. After WWII and the Holocaust, there was a need to protect people from the State, ensure that the atrocities would never be repeated and safeguard fundamental rights. Furthermore, there were discussions about transforming relationships in international law, so that individuals could protect their rights internationally as well. The CoE declared its peace orientation, based on justice and international cooperation, as a vital element for the preservation of human society and civilisation. According to Article 1, paragraph 1, of the Council’s Statute, ‘The aim of the Council of Europe is to achieve a greater unity between its members for the purpose of safeguarding and realising the ideals and principles which are their common heritage and facilitating their economic and social progress’.However, greater unity cannot be achieved without peace and human rights protection.In the new European era, the issue of human rights has grown into a key topic. The CoE is part of the European architecture and its role should not be seen in cooperation with other international organisations and states. The ideals and principles of the CoE have been codified in more than 200 treaties drawn up by the CoE over 75 years. These documents, coupled with the judgments of the European Court of Human Rights (known as the Strasbourg Court; ECtHR), the recommendations and resolutions of the Committee of Ministers, the Parliamentary Assembly and the Congress of Local and Regional Authorities, and the recommendations of the Venice Commission and other CoE’s monitoring and advisory bodies, including the Commissioner for Human Rights, are the cornerstones of a unique system that protects the fundamental rights of more than 700 million people in 46 Member States. Keywords: CoE, human rights, fundamental freedoms, peace, human dignity, rule of law, democracy